FIRST RECORD OF 13 SPECIES OF TENTHREDO LINN. (HYMENOPTERA : TENTHREDINIDAE) FROM INDIA - SINGH, DEWINDER; SAINI, MALKIAT S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
13 species are added to the list of Indian Tenth redo. Synonymy (if any), number of specimens examined, distribution, population variation (if significant) and some remarks have been provided for each of the enlisted species. Representatives of these newly recorded species will be deposited to the Pusa National Collection, IARI, New Delhi, after this wor' is published.